Banking supervisory architecture and sovereign risk - Cuadros-Solas, Pedro J.; Salvador, Carlos; Suárez, Nuria (Journal of Financial Stability, 2025)
This paper investigates whether the design of the banking supervisory architecture impacts sovereign risk. Exploiting the implementation of the Single Supervisory Mechanism (SSM) in Europe, we provide evidence that sovereign risk – measured by sovereign ratings – is lower after the largest banks shift from national to supranational supervision. The impact of SSM implementation is shaped by the characteristics of the banking sector and the country’s institutional setting. Using specific bank-level data, we also find that increased bank resilience (banking stability) and reduced volatility of bank credit (credit stability) in the economy underlie the relationship between banking supervision and sovereign risk. The results hold when considering CDS spreads as an alternative measure of sovereign risk and after conducting several robustness tests.